Odločevalna matrika za izbor ekološko ustrezne tehnologije pri proizvodnji zelenih sekancev - Triplat, Matevž (Acta silvae et ligni, 2016)
Due to the rising prices of fossil fuels and promotion of renewable energy sources, we recently witnessed the growing demands of the public for the exploitation of renewable biomass potentials. Slovenian legislation very rigidly defines utilization of logging residues and the production of green chips. In practice, this allows uncontrolled actions that bring new technologies, which raises a number of issues particularly with regard to environmental and ecological burdens. This paper presents a methodological approach used at design of the decision-making tool for the selection of environmentally friendly harvesting system in the production of green woodchips by considering various ecological and technological factors. Basically, a threestep methodological process is used, where in the first step soil and terrain are defined, in the second step, harvesting systems taking into account the diversity in terms of economic impact and ecological suitability are proposed and, last but not least, harvesting systems are placed into decision matrix taking into account technological and environmental constraints of different harvesting systems. The article also suggests 13 harvesting systems that are arranged into decision-making matrix taking into account the ecological, technological aspects in the production of green woodchips.
Keywords: harvesting system; tehnološki modeli; production; proizvodnja; supply chain; proizvodne verige; poškodbe tal; soil damage; green wood chips; zeleni lesni sekanci